Spermidine is essential for normal proliferation of trypanosomatid protozoa - González, N.S. (2001)
Trypanosomatid parasites containing a metabolically unstable ornithine decarboxylase (ODC) are naturally resistant to high levels of α-difluoromethylornithine (DFMO) because this ODC inhibitor, though causing a drastic reduction of intracellular putrescine, elicits only a moderate decrease of the spermidine endogenous pool. In this study we have used a combination of DFMO with cyclohexylamine (CHA; bis-cyclohexylammonium sulfate), an inhibitor of spermidine synthase, to reach a more complete depletion of spermidine. Under these conditions we have observed the arrest of proliferation not only in trypanosomatids with stable ODC but also in parasites with an enzyme of high turnover rate. In all cases the reinitiation of proliferation occurred only after the addition of exogenous spermidine, and neither putrescine nor spermine were able to induce the same effect. © 2001 Federation of European Biochemical Societies. Published by Elsevier Science B.V. All rights reserved.